Unilateral Isolated Proximal Femoral Focal Deficiency - Emek Doğer; Şule Y. Köpük; Yiğit Çakıroğlu; Özgür Çakır; Gülseren Yücesoy (Case Reports in Obstetrics and Gynecology)
Objective. To discuss a patient with a prenatal diagnosis of unilateral isolated femoral focal deficiency. Case. Antenatal diagnosis of unilateral isolated femoral focal deficiency was made at 20 weeks of gestation. The length of left femur was shorter than the right, and fetal femur length was below the fifth percentile. Proximal femoral focal deficiency was diagnosed. After delivery, the diagnosis was confirmed with skeletal radiographs and magnetic resonance imaging. In prenatal ultrasonographic examination, the early recognition and exclusion of skeletal dysplasias is important; moreover, treatment plans should be initiated, and valuable information should be provided to the family.